HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KELENTUKAN PERGELANGAN TANGAN DENGAN HASIL SMASH BOLA VOLI PADA PEMAIN CLUB PUTRI RIMA BUKIT KAPUR DUMAI - Yuli Monica Ramadani; Slamet Slamet; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Problems encountered in the women's volleyball club RIMA Bukit Kapur Dumai found several expected phenomena: found the results of smash by athletes are still not optimal, this is caused by physical athletes not optimal such as leg muscle explosiveness and completeness of athletic sports equipment that is not optimal, so the results of smashes that are done are not powered and are easily captured. The purpose of this study was to study the relationship of leg muscle explosive power, the flexibility of hand relationships and the relationship of leg muscle explosive power and hand motions together with the results of the smash of the Putri Rima Bukit Kapur Club in Dumai. This research was conducted in the field of the Bukit Kapur Dumai Princess Rima Club, Simpang Gambir, Dumai and was conducted in March - August 2019. The population in this study was the women's volleyball club in Bukit Kapur Dumai as many as 14 people. This research was conducted by using research studies that discuss the distant variables - variables on factors related to other factors. Based on the analysis obtained a coefficient of r count (0.724)> r table (0.684), thus Ha is accepted. Associated with the relationship between leg muscle explosive power and flexibility of the hands with the results of smashes, where the provisions have to do with variables Key Words: Leg Muscle Explosive Power, Wrist Flexion, Smash Results